Analysis of The Effect of Work Environment and Knowledge Sharing on Employee Performance in Innovative Behavior Mediation - Suryanto Suryanto; Syamsul Hadi; Didik Subiyanto (Universitas Muhammadiyah Yogyakarta, 2023)
Purpose - This study aims to analyze the effect of the work environment and Knowledge sharing on employee performance by mediating innovative behavior.Design/methodology/approach - The sampling method used was the census method. The research subjects were the Settlement Infrastructure Agency for DI Yogyakarta Region employees, while data retrieval employed a questionnaire for 146 respondents. However, questionnaires only processed data for 100 respondents. Data analysis used Partial Least Square (PLS) inferential, variance-based SEM with SmartPLS Version 3.0 software.Findings - The results showed that the work environment and knowledge sharing had a positive and significant effect on employee performance, the work environment had no effect on innovative behavior or was not proven, knowledge sharing had a positive and significant effect on innovative behavior, innovative behavior had a positive and significant effect on employee performance. The mediation results showed that innovative behavior could partially mediate the influence of the work environment and Knowledge sharing on employee performance. The role of innovative behavior in mediating the work environment and Knowledge sharing had a positive and significant effect on employee performance, so, in this study, innovative behavior could mediate the work environment and Knowledge sharing on employee performance.Research limitations/implications – Respondents who returned the questionnaires to the researchers were not 100% of the total sample population, so the analysis results were not the same as the hypothesis.Originality/value - The novelty of this research is to examine the role of mediating innovative behavior in the influence of KS and the work environment on employee performance in public service employees who have different characteristics when compared to employees of non-public organizations.